Perancangan Sistem Tracking Procurement Berbasis Web dengan Integrasi Rekam Jejak Persetujuan (Audit Trail) - Valent Laorens; Dean Prananta; Venny Ponggawa; Franky Manoppo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Structured and integrated procurement management is a primary pillar for business sustainability in the digital era. This research focuses on resolving procurement administration issues at PT. X, which relies heavily on physical documents (WD, PRS, PO, and RR), leading to a high risk of lost audit trails, slow approval processes, and a lack of transparency. This study aims to design a web-based procurement tracking system that centrally integrates all procurement stages. System development adopted the Waterfall method, chosen specifically for its ability to accommodate the company's rigid, sequential, and strictly standardized bureaucratic flow across departments. The system was built using the Laravel framework and MySQL database. Black Box Testing confirmed that all modules operate validly. The main contribution of this research is the integration model of a real-time audit trail tracking across departments. Quantitatively, the system's implementation is estimated to significantly reduce the approval lead time from an average of 3-5 workdays to under 24 hours and eliminate the risk of document loss to 0%. These results prove that the digitalization of the tracking system provides measurable positive impacts for PT. X's operations.